Physiochemical and optical properties of chitosan based graphene oxide bionanocomposite - Kumar, Santosh (2014)
In the present investigation an ecofriendly approach and a simple homogeneous solution casting method led to the development of biodegradable chitosan/graphene oxide bionanocomposites. The formation of bionanocomposite was confirmed by UV–vis, FT-IR, Raman spectroscopy, XRD, and further evaluated by thermogravimetric analysis (TGA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The circular dichroism (CD) study of chitosan/graphene oxide revealed that the intensity of the negative transition band at wavelength of 200–222 nm decreased with the different pH of chitosan/graphene oxide solutions. It was also found that the pH conditions affect the interaction between chitosan and graphene oxide. Optical properties of chitosan/graphene oxide are evaluated by photoluminescence (PL) spectroscopy which showed blue shift at excitation wavelength of 255 nm compared to graphene oxide. These results strongly suggest that the bionanocomposite materials may open new vistas in biotechnological, biosensor and biomedical applications.